Evaluation of methods for centrifugation and hydrothermal treatment for obtaining of calcium phosphate nanoparticles (2017)
(Eng) Calcium phosphates are ceramics materials used in the manufacture of bone substitutes, due to their composition which is similar to the bones, they are bioactive, osteoconductivity and works in favor of forming porous structures, allowing vascularization and cell adhesion; furthermore they stand out for their biocompatibility. They are currently employed in the replacement of bone tissue in several clinical applications such as bone cements and fillers. Within this paper, nanoparticles of different calcium phosphates were obtained and characterized by two methods reported in the literature, centrifugation and hydrothermal treatment from precipitation reaction. The powders were characterized by XRD and FE-SEM. The results prove that both methods are suitable for the obtaining of nanoparticles of calcium phosphates, which is verified in the micrographs obtained where different morphologies are observed. Particles in nanoscale for most powders obtained have average diameter between 44.98 and 82.21 nm and average length between 123.91 and 151.48 nm. Diffractograms by both methods show the presence of calcium phosphates with different potential applications in bone tissue engineering, for the hydrothermal method was found that the temperature and time are major factors during stabilizing of phases. From this study it was concluded that both synthesis methods are suitable for obtaining nanoparticles and stabilization of different phases of calcium phosphate, being protocols 1, 3 and 4 the most suitable for biomedical applications.